Differentiated baroreflex modulation of sympathetic nerve activity during deep brain stimulation in humans. - Sverrisdóttir, Y; Green, A; Aziz, T; Bahuri, N; Hyam, J; Basnayake, S; Paterson, D (2014)
Targeted electric deep brain stimulation in midbrain nuclei in humans alters cardiovascular parameters, presumably by modulating autonomic and baroreflex function. Baroreflex modulation of sympathetic outflow is crucial for cardiovascular regulation and is hypothesized to occur at 2 distinct brain locations. The aim of this study was to evaluate sympathetic outflow in humans with deep brain stimulating electrodes during ON and OFF stimulation of specific midbrain nuclei known to regulate cardiovascular function. Multiunit muscle sympathetic nerve activity was recorded in 17 patients undergoing deep brain stimulation for treatment of chronic neuropathic pain (n=7) and Parkinson disease (n=10). Sympathetic outflow was recorded during ON and OFF stimulation. Arterial blood pressure, heart rate, and respiratory frequency were monitored during the recording session, and spontaneous vasomotor and cardiac baroreflex sensitivity were assessed. Head-up tilt testing was performed separately in the patients with Parkinson disease postoperatively. Stimulation of the dorsal most part of the subthalamic nucleus and ventrolateral periaqueductal gray resulted in improved vasomotor baroreflex sensitivity, decreased burst frequency and blood pressure, unchanged burst amplitude distribution, and a reduced fall in blood pressure after tilt. Stimulation of the dorsolateral periaqueductal gray resulted in a shift in burst amplitude distribution toward larger amplitudes, decreased spontaneous beat-to-beat blood pressure variability, and unchanged burst frequency, baroreflex sensitivity, and blood pressure. Our results indicate that a differentiated regulation of sympathetic outflow occurs in the subthalamic nucleus and periaqueductal gray. These results may have implications in our understanding of abnormal sympathetic discharge in cardiovascular disease and provide an opportunity for therapeutic targeting.